2022
DOI: 10.3389/fmicb.2022.911757
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Persistent Effects of Acute Exposure to AFB1 on Rat Liver

Abstract: Aflatoxin B1 (AFB1) has mutagenesis, carcinogenesis and teratogenesis effects and mainly found in food crops and their processed foods. AFB1 exposure can cause acute or chronic liver poisoning, but there were few studies on the persistent effects of acute AFB1 exposure on the liver. In this study, rat liver injury models were established 2 and 7 days after single exposure to high and low doses of AFB1. The persistent effects of AFB1 single acute exposure (ASAE) on rat liver were analyzed from the phenotypic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…In fact, the high concentration of COS interventions was almost as potent as the liver protector SIL. AST and ALT are frequently used tests to determine whether the liver injury has occurred [27], it is obvious that AFB 1 caused irreversible damage to the liver function of the medaka after intraperitoneal injection, and the results of this experiment are similar to those of other papers on AFB 1 -induced liver injury [28].…”
Section: Discussionsupporting
confidence: 76%
“…In fact, the high concentration of COS interventions was almost as potent as the liver protector SIL. AST and ALT are frequently used tests to determine whether the liver injury has occurred [27], it is obvious that AFB 1 caused irreversible damage to the liver function of the medaka after intraperitoneal injection, and the results of this experiment are similar to those of other papers on AFB 1 -induced liver injury [28].…”
Section: Discussionsupporting
confidence: 76%
“…At the same time, different intake times and doses of AFB 1 can cause acute or chronic liver poisoning. In this paper, the AFB 1 dose of 1 mg/kg BW was determined on the basis of existing studies, and the equivalent human dose was calculated based on the body surface area conversion factor (Yan et al 2022 ; Reagan-Shaw et al 2008 ). The result showed that the human intake of AFB 1 was 0.21 mg/kg, which was lower than the LD50 of AFB 1 .…”
Section: Introductionmentioning
confidence: 99%